Penerapan Kebijakan Protokol Kesehatan dalam Pencegahan Covid-19 - Hasma Hasma; Musfirah Musfirah; Rusmalawati Rusmalawati (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; In 2020, the corona virus spread, a new type of virus (SARS-CoV-2) whose disease is called Corona Virus Disease 2019 (COVID-19). Corona virus is a virus that comes from animals and is transmitted through humans. Aim; know the description of the implementation of health protocol policies in the prevention of COVID-19. Method; The type of research used is qualitative research with a phenomenological approach with a total of 5 informants consisting of 1 key informant and 3 regular informants and 1 additional informant. Data were analyzed (content analysis) using interview and observation guidelines. Results; found that the implementation of health protocol policies in preventing COVID-19 has not been fully implemented because the community does not have the awareness to apply it in everyday life. Conclusion; the application of the use of masks, washing hands and social distancing have not been fully implemented properly, this is because there are still many residents who are active outside the home and still ignore.